Synthesis of biogenic silver nanoparticles using Althaea officinalis as reducing agent: evaluation of toxicity and ecotoxicity - Rheder, Diogo Torres; Guilger, Mariana; Bilesky-José, Natália; Germano-Costa, Taís; Pasquoto-Stigliani, Tatiane; Gallep, Tatiane Balbo Batista; Grillo, Renato [UNESP]; Carvalho, Cleoni dos Santos; Fraceto, Leonardo Fernandes [UNESP]; Lima, Renata (Springer Nature, 2018)
Silver nanoparticles (AgNPs) are known mainly because of their bactericidal properties. Among the different types of synthesis, there is the biogenic synthesis, which allows the synergy between the nanocomposites and substances from the organism employed for the synthesis. This study describes the synthesis of AgNPs using infusion of roots (AgNpR) and extract (AgNpE) of the plant Althaea officinalis. After the synthesis through reduction of silver nitrate with compounds of A. officinalis, physico-chemical analyzes were performed by UV-Vis spectroscopy, nanoparticles tracking analysis (NTA), dynamic light scattering (DLS) and scanning electron microscopy (SEM). Toxicity was evaluated through Allium cepa assay, comet test with cell lines, cell viability by mitochondrial activity and image cytometry and minimal inhibitory concentration on pathogenic microorganisms. Biochemical analyzes (CAT - catalase, GPx - glutathione peroxidase e GST - glutationa S-transferase) and genotoxicity evaluation in vivo on Zebrafish were also performed. AgNpE and AgNpR showed size of 157 ± 11 nm and 293 ± 12 nm, polydispersity of 0.47 ± 0.08 and 0.25 ± 0.01, and zeta potential of 20.4 ± 1.4 and 26.5 ± 1.2 mV, respectively. With regard to toxicity, the AgNpE were the most toxic when compared with AgNpR. Biochemical analyzes on fish showed increase of CAT activity in most of the organs, whereas GPx showed few changes and the activity of GST decreased. Also regarding to bactericidal activity, both nanoparticles were effective, however AgNpR showed greater activity. Althaea officinalis can be employed as reducing agent for the synthesis of silver nanoparticles, although it is necessary to consider its potential toxicity and ecotoxicity.